2021
DOI: 10.1212/nxi.0000000000000981
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate in Relapsing-Remitting Multiple Sclerosis

Abstract: ObjectiveTo assess the safety and efficacy of epigallocatechin-3-gallate (EGCG) add-on to glatiramer acetate (GA) in patients with relapsing-remitting multiple sclerosis (RRMS).MethodsWe enrolled patients with RRMS (aged 18–60 years, Expanded Disability Status Scale [EDSS] score 0–6.5), receiving stable GA treatment in a multicenter, prospective, double-blind, phase II, randomized controlled trial. Participants received up to 800 mg oral EGCG daily over a period of 18 months. The primary outcome was the propor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Other clinical trials also failed to show a treatment effect of EGCG: The SUNIMS trial ( 63 ) reported no treatment effect of EGCG on clinical or MRI measures in RRMS patients. Moreover, a recently published study demonstrated no impact of EGCG after 48 weeks of treatment on disease progression in multiple system atrophy ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical trials also failed to show a treatment effect of EGCG: The SUNIMS trial ( 63 ) reported no treatment effect of EGCG on clinical or MRI measures in RRMS patients. Moreover, a recently published study demonstrated no impact of EGCG after 48 weeks of treatment on disease progression in multiple system atrophy ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their efficacy endpoint was the development of new hyperintense lesions on T2-weighted brain MRIs. The 18-month treatment with 800 mg/day oral EGCG added to GA showed no superiority in MRI findings and clinical activity, compared to placebo [ 54 ]. A double-blind clinical trial analyzed the mechanisms of antioxidant therapy on MS patients.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the administration of 800 mg of EGCG on a daily basis for six months increased N-acetyl aspartate levels in the brain, revealing a neuroprotective effect; however, the study had to be stopped because five out of seven patients on the Polyphenon E group had abnormal liver function tests and the researchers concluded that Polyphenon E may increase the risk of hepatotoxicity [ 58 ]. In other reviewed articles, safety of EGCG treatment was assessed, concluding that it was a safe medication with similar adverse events in the placebo and treatment groups [ 54 , 55 ]. Polyphenon E contains other polyphenols besides EGCG and may have small amounts of caffeine, metabolized in the liver, which may explain these safety differences.…”
Section: Resultsmentioning
confidence: 99%
“…We recruited 255 subjects including 195 patients with MS and 60 healthy controls in a multi-centric study in four MS centers (Hospital Clinic Barcelona -IDIBAPS (n=69), Karolinska Institute (n=64), University of Zurich (n=40), and Charité University (n=82)). Healthy donors, untreated patients and patients treated with IFNB, GA, NTZ, and FTY were described before in an accompanying study [26], whereas the participants in a trial testing epigallocatechin-gallate (EGCG) at Charité University were described in [27]. Characteristics of the clinical cohorts: mean age: 43.1+11.3 years; disease duration: 8.7+ 7.7 years; median Expanded Disability Status Scale (EDSS): 2.0 (0-6.0); disease subtype: 24 clinically isolated syndrome (CIS), 129 relapsing-remitting MS (RRMS), 6 secondary-progressive MS (SPMS), and 36 primaryprogressive MS (PPMS); untreated: 93 and 60 healthy controls (Table 2).…”
Section: Subjects and Clinical Cohortsmentioning
confidence: 99%
“…The data from clinical studies has been published by Kotelnikova et al in [26], while the data from the EGCG clinical trial has been published by Bellmann-Strobl et al in [27]. All data generated in this study are available on Github (http://github.com/saezlab/combiMS) [73], including all data transformations from xMAP raw measurements to modelling-transformed as shown in Fig.…”
Section: Supplementary Informationmentioning
confidence: 99%